Accuracy of fine needle aspiration biopsy to diagnose lymphadenopathy in Dr.Sardjito General Hospital, Yogyakarta, Indonesia - Ery Kus Dwianingsih; Claudia Priska Adelin; Andre Stefanus Panggabean; Linda Pratiwi; Naomi Yoshuantari; Mardiah Suci Hardianti; I Indrawati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Lymphadenopathy is a non-specific enlargement of lymph nodes which may be caused by infection, cancer, or autoimmune disease. To date, only a few studies reported the diagnostic value of fine-needle aspiration biopsy (FNAB) in lymphadenopathy. This study was performed to evaluate diagnostic reliability of FNAB for benign and malignant lymphadenopathy. This was a retrospective cross-sectional study. The obtained data were statistically analyzed for its sensitivity, specificity, and accuracy. Out of 126 collected FNAB cases with histopathological confirmed results in Dr. Sardjito General Hospital, Yogyakarta, 85 (67.4%) were malignant lymphadenopathy, consisting of 42 metastatic tumor cases, 38 non-Hodgkin lymphoma (NHL) cases, and 4 Hodgkin lymphoma (HL) cases.The overall diagnostic sensitivity, specificity, and accuracy of FNAB in lymphadenopathy was 85.88, 70.73, and 80.95%, respectively. In diagnosing metastatic tumors, FNAB had sensitivity of 83.33%; specificity of 89.28%; and accuracy of 87.3%. The sensitivity, specificity, and accuracy of FNAB in diagnosing NHL was 60.52, 94.31, and 84.12%, respectively. FNAB had a sensitivity of 25%, specificity of 95,90%, and accuracy of 93.65% to diagnose HL. Meanwhile, the accuracy of FNAB in diagnosing malignancies in generalized lymphadenopathy, head-neck lymphadenopathy, and inguinal lymphadenopathy was 90.90; 81.39 and 44.44%, respectively. In conclusion,FNAB has moderate diagnostic value in diagnosing overall malignant lymphadenopathy, including metastatic tumors. FNAB also has some limitations in diagnosing NHL and HL, with sensitivity less than 70% for both diseases. However, it has high accuracy to diagnose generalized lymphadenopathy.